Research on the influencing factors of anti-skid performance evaluation of asphalt pavement based on lateral force testing system - Zhang, Xiaoying; Chang, Rong; Xu, Zhixiang; Wang, Jie; Tan, Zhibing (Frontiers in Materials, 2024)
This article conducts experimental research on the influencing factors of the anti-skid performance testing system SCRIM for asphalt pavement. Studied the distribution pattern of anti-skid performance test results of the testing system under different testing speeds, test tires, temperature, water film thickness, test wheel position, tire wear degree, and other factors. Revealed the influence law of various influencing factors on the anti-skid performance of asphalt pavement. The test results indicate that the SFC test value decreases with the increase of vehicle speed. The test results of tires made of different materials vary greatly, and tires with wear exceeding 3mm cannot be used for testing. The influence of water film thickness on the measured values varies depending on the SFC level. The SFC measurement value of the normal trajectory of the vehicle's driving wheel track is the smallest, and the measurement value of the left trajectory is greater than that of the right trajectory. The SFC measurement decreases as the tire wear increases.